2017
DOI: 10.1016/j.trsl.2016.07.012
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution characterization of the human microbiome

Abstract: The human microbiome plays an important and increasingly recognized role in human health. Studies of the microbiome typically employ targeted sequencing of the 16S rRNA gene, whole metagenome shotgun sequencing, or other meta-omic technologies to characterize the microbiome's composition, activity, and dynamics. Processing, analyzing, and interpreting these data involve numerous computational tools that aim to filter, cluster, annotate, and quantify the obtained data and ultimately provide an accurate and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 180 publications
(181 reference statements)
0
48
0
Order By: Relevance
“…Recently, a plethora of comparative studies have identified intriguing associations between the composition of the microbiome and numerous diseases including various metabolic disorders (Greenblum et al, 2012; Karlsson et al, 2014; Qin et al, 2013), malignancies (Schulz et al, 2014), autoimmune diseases (Scher et al, 2013), and neurological developmental disorders (Hsiao et al, 2013). Such studies can take two different approaches to profile the composition of the microbiome (Noecker et al, 2016). The first approach focuses on taxonomy, aiming to profile the abundances of different microbial clades in each sample, either by targeted sequencing of the ribosomal 16S gene and operational taxonomic units clustering (Caporaso et al, 2010; Schloss et al, 2009) or by shotgun metagenomic sequencing and quantification of clade-specific marker genes’ abundances (Segata et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a plethora of comparative studies have identified intriguing associations between the composition of the microbiome and numerous diseases including various metabolic disorders (Greenblum et al, 2012; Karlsson et al, 2014; Qin et al, 2013), malignancies (Schulz et al, 2014), autoimmune diseases (Scher et al, 2013), and neurological developmental disorders (Hsiao et al, 2013). Such studies can take two different approaches to profile the composition of the microbiome (Noecker et al, 2016). The first approach focuses on taxonomy, aiming to profile the abundances of different microbial clades in each sample, either by targeted sequencing of the ribosomal 16S gene and operational taxonomic units clustering (Caporaso et al, 2010; Schloss et al, 2009) or by shotgun metagenomic sequencing and quantification of clade-specific marker genes’ abundances (Segata et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to 16S rRNA gene sequencing, microbiome characterization methodologies have expanded to other “-omics” approaches to include whole genome shotgun sequencing, RNAseq, and metabolomics, which more precisely delineate bacterial community structure, gene presence/expression, and metabolic activity [7]. Use of these methodologies has illuminated that the microflora have profound effects on human health such as altering cytokine profiles, influencing inflammatory immune responses, and altering metabolites [811].…”
Section: How Antibiotic-induced Microbiome Alteration Affects the Canmentioning
confidence: 99%
“…Researchers across many life and clinical science disciplines are increasingly exploring the impact of microbes and microbial community dynamics. Concomitant increases are occurring in microbiome data generation as well as in the development of computational tools to perform data analysis (Aguiar-Pulido et al, 2016;Morgan and Huttenhower, 2014;Noecker et al, 2017). However, many researchers studying the microbiome lack resources or specialized skills for managing and analyzing the large, multi-dimensional datasets associated with metagenomic analyses.…”
Section: Introductionmentioning
confidence: 99%